Review Of surgery of VSD in Ibn Al-Nafees Teaching Hospital - Adel Kh. Dawood (مجلة كلية الطب, 2015)
Background: Ventricular septal defect (VSD) is the most commonly recognized congenital heart defect. Isolated VSDs represent about 20-30% of all congenital cardiac malformations and have a prevalence of 1- 2 % per 1,000 live births. Objective: This study is planned to review the outcome of surgical closure of VSD at Ibn Al-Nafees Teaching Hospital (Department Cardiac Surgery) Baghdad/Iraq. Patients and methods: This study includes 50 cases of VSD both isolated and VSD associated with other congenital malformations admitted and underwent surgical repair of age range between 3 to 28 years and weight range between 9 to 80 kg. Different type of VSD, were found and repaired whether isolated or with other associated congenital anomalies which dealt with at the same time. Results: The following VSD types were found: 40 peri- membranous 80%, 3 outlet 6%, 5 inlet 10% and 2 muscular 4%. Additional surgery were 3 pulmonary valvotomy 6%, 3 right ventricular outflow patch 6%, 7 closure of atrial septal defect 14%, 2 excision of subaortic ridge 4% and 2 aortic valve replacement 4%. One patient required reoperation for bleeding. Four patients had complete heart block that required temporary pacemaker. Over all operative mortality were two cases (4%), median postoperative hospital length stay was 7 days (range 5-18 days). Conclusions: Surgical closure of VSD is a safe and effective therapy in isolated VSD or VSD with other malformations and reoperation is minimal. Other cardiac malformations can be repaired at the same time with the closure of VSD with good results and very minimal complications.